gSeaGen code by KM3NeT: An efficient tool to propagate muons simulated with CORSIKA - S. Aiello; A. Albert; A.R. Alhebsi; M. Alshamsi; S. Alves Garre; A. Ambrosone; F. Ameli; M. Andre; L. Aphecetche; M. Ardid; S. Ardid; H. Atmani; et al. (Computer Physics Communications, 2025)

Linking conventional activated sludge treatment plant performances for micropollutants removal to environmental risk and SimpleTreat model assessment - C. Di Marcantonio; A. Chiavola; D. Spagnoli; B. Meşe; F. Margarita; V. Gioia; A. Frugis; S. Leoni; G. Cecchini; M. Spizzirri; M. R. Boni (International Journal of Environmental Science and Technology, 2024)
The attention to the contaminants of emerging concerns or micropollutants is continuously rising, also stimulated by the new initiatives at European level. The present study focuses on the removal of target micropollutants in a conventional activated sludge wastewater treatment plant which is the most common system and considered a source of micropollutants to the environment. The aims were to evaluate the removal efficiency of different stages of the wastewater treatment plant and to conduct the Environmental Risk Assessment on the final effluent. As indicated by the European’s guidelines on Environmental Risk Assessment, the SimpleTreat4.1 model was applied to this purpose: different values of the biodegradation constant, which represents the key factor for modelling, were applied, and the effects on the quality of prediction were evaluated. The evaluations were carried out thorough 3-year monitoring activity in a full-scale wastewater treatment plant on 10 micropollutants belonging to the classes of illicit drugs, pharmaceuticals and psychoactive. The model was found statistically not satisfactory for most of the investigated micropollutants. A better prediction was obtained when the biodegradation constant was calculated based on the full-scale data. Nonetheless, the results obtained in terms of risk were considered acceptable and comparable among each other. Graphical abstract

Embedded software of the KM3NeT central logic board - S. Aiello; A. Albert; S. Alves Garre; Z. Aly; A. Ambrosone; F. Ameli; M. Andre; E. Androutsou; M. Anghinolfi; M. Anguita; L. Aphecetche; M. Ardid; et al. (Computer Physics Communications, 2024)

Phenolics and antioxidant activity in different cultivars/clones of Vitis vinifera L. seeds over two years - B. Giannini; N. Mulinacci; G. Pasqua; M. Innocenti; A. Valletta; F. Cecchini (Plant Biosystems, 2016)

Variation in fructooligosaccharide contents during plant development and in different cultivars of durum wheat - A. Paradiso; C. Cecchini; E. Greco; M. G. D'Egidio; L. De Gara (Plant Biosystems, 2008)

Immunohistochemical Evaluation of Estrogen Receptor β Expression in Calf Prostates with Squamous Metaplasia - R. Stocchi; G. Renzoni; S. Rea; S. Cecchini; A. R. Loschi (Veterinary Research Communications, 2006)

Two genetically related strains of Tuber borchii produce Tilia mycorrhizas with different morphological traits - D. Sisti; G. Giomaro; M. Cecchini; A. Faccio; M. Novero; P. Bonfante (Mycorrhiza, 2003)

Enterococcus spp. produces slime and survives in rat peritoneal macrophages - Lucilla Baldassarri; Roberto Cecchini; Lucia Bertuccini; Maria G. Ammendolia; F. Iosi; Carla R. Arciola; Lucio Montanaro; Roberta Di Rosa; Giovanni Gherardi; Giordano Dicuonzo; Graziella Orefici; Roberta Creti (Medical Microbiology and Immunology, 2001)

Anatomical and morphological characterization of mycorrhizas of five strains of Tuber borchii Vittad - G. Giomaro; A. Zambonelli; D. Sisti; M. Cecchini; V. Evangelista; V. Stocchi (Mycorrhiza, 2000)

Influence of environmental temperature and water oxygen concentration on gas diffusion distance in sea bass (Dicentrarchus labrax, L.) - M. Saroglia; S. Cecchini; G. Terova; A. Caputo; A. De Stradis (Fish Physiology and Biochemistry, 2000)

Ascorbate dynamics in embryos and larvae of sea bass and sea bream, originating from broodstocks fed supplements of ascorbic acid - G. Terova; M. Saroglia; Z. Gy. Papp; S. Cecchini (Aquaculture International, 1998)

Variability of Surface Air Temperature in Italy 1870-1980 - T. Nanni; G. Lo Vecchio; S. Cecchini (Theoretical and Applied Climatology, 1998)

Force responses to fast ramp stretches in stimulated frog skeletal muscle fibres - M. A. Bagni; G. Cecchi; E. Cecchini; B. Colombini; F. Colomo (Journal of Muscle Research and Cell Motility, 1998)

Analysing the performance of a micro soil solution sampling device in a laboratory examination and a field experiment - A. Spangenberg; G. Cecchini; N. Lamersdorf (Plant and Soil, 1997)

Abstracts of presentations on plant protection issues at the fifth international Mango Symposium Abstracts of presentations on plant protection issues at the Xth international congress of Virology - J. E. Peña; M. Wysoki; Gajendra Singh; Nancy Boscán de M.; Freddy J. Godoy; A. Obligado; C. J. Rossetto; I. J. A. Ribeiro; P. B. Gallo; N. B. Soares; J. C. Sabino; A. L. M. Martins; et al. (Phytoparasitica, 1997)